The Determinants of Foreign Direct Investment in Pakistan: an Empirical Investigation (The Pakistan Development Review, 2003)
The changing modes of international transactions and the cross-border mobilisation of factor resources, in pursuance of transnational production, constitute new dimensions for sustained economic growth. Foreign Direct Investment (an influential element of this process) is defined as the source of acquisition of managerial control by a business enterprise of a foreign country over a business activity in a host country [Graham (1982)]. The changing perceptions and more attractive policies of the host developing nations have changed the destinations of FDI flows from industrially developed countries to high growth developing centres. FDI stock held by developing countries has risen from $ 132.95 billion in 1980 to $ 1438.48 billion in 1999. Their share in inward stock has reached to 30.14 percent in 1999 as against 26.2 percent in 1980. FDI inflows during this period were raised from $ 4.42 billion to $ 208.0 billion, at an annual growth rate of 22.5 percent while GDP growth rate for that period was 3.9 percent.